Kunst van heden in België Antwerpen. (Antwerpen : Hessenhuis, 1964)
Aebly, Albert ; Alechinsky, Pierre ; Anthoons, Willy ; Antoine, Paul ; Arnould, Marcel ; Burssens, Jan ; Frey, Alice ; Geenens, Robert ; Hanrez, Paul ; Jans, Jos ; Malfait, Hubert ; Mortier, Antoine ; Notebaert, Marcel ; Roulin, Félix ; Strebelle, Jean-Marie ; Van Elzen, Staf ; Van Lint, Louis ; etc.
Kunst van heden in België Antwerpen, Hessenhuis, Antwerpen, 5 september - 18 oktober 1964
boek
Keywords: België